Strategies to Design Bipolar Small Molecules for OLEDs: Donor-Acceptor Structure and Non-Donor-Acceptor Structure - Duan, Lian; Qiao, Juan; Sun, Yongduo; Qiu, Yong (Advanced materials (Weinheim), 2011)
Organic light‐emitting diodes (OLEDs) have attracted great attention because of their potential applications in full‐color displays and solid‐state lights. In the continual effort to search for ideal materials for OLEDs, small molecules with bipolar transporting character are extremely attractive as they offer the possibility to achieve efficient and stable OLEDs even in a simple single‐layer device. In this Research News, we review the two design strategies of bipolar materials for OLEDs: molecules with or without donor‐acceptor structures. The correlation between the experimental results and theoretical calculations of some of the materials is also discussed. Small molecules with bipolar transporting characters are extremely attractive as they offer the possibility to achieve efficient and stable organic light‐emitting diodes (OLEDs). In this article we review the two design strategies for bipolar materials for OLEDs: with or without donor‐acceptor structure. The correlation between the experimental results and theoretical calculations of some of the materials is also discussed.